2015
DOI: 10.2807/1560-7917.es2015.20.21.21136
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analyses of Francisella tularensis strains confirm disease transmission from drinking water sources, Turkey, 2008, 2009 and 2012

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 27 publications
1
32
0
1
Order By: Relevance
“…6 Similar data were reported by Turkish researchers. [17][18][19][20][21] In contrast French outbreak described glandular form in 46% and ulceroglandular tularemia in 26% of cases. 22 The variety of clinical forms is infl uenced by complex factors as transmission, mechanism of entry and infective dose.…”
Section: Discussionmentioning
confidence: 99%
“…6 Similar data were reported by Turkish researchers. [17][18][19][20][21] In contrast French outbreak described glandular form in 46% and ulceroglandular tularemia in 26% of cases. 22 The variety of clinical forms is infl uenced by complex factors as transmission, mechanism of entry and infective dose.…”
Section: Discussionmentioning
confidence: 99%
“…F. tularensis can only persist in fresh water for a limited time (27, 28), and is seasonally recovered from natural bodies of water, suggesting recurrent cycles of contamination (7, 31). Early soviet researchers reported that a single infected animal could contaminate 500,000L of water (44), and infected animals are indeed implicated in virtually all cases of water contamination with F. tularensis (68, 1012, 16, 17, 19, 22, 26, 31–33). To survive an osmotic downshock, such as that encountered when going from a mammalian host to fresh water, bacteria rely on mechanosensitive channels which act as ‘pressure relief valves’.…”
Section: Discussionmentioning
confidence: 99%
“…Outbreaks of tularemia from contaminated drinking water have been reported in at least 10 countries, totaling thousands of cases. Such outbreaks have been reported in Turkey (68), Sweden (9), Germany 10), Norway 11–13), Russia (14, 15), Bulgaria (16, 17), Kosovo (18, 19), The Czech Republic(20), Italy (21, 22) and the Republic of Georgia (23). Isolated cases of tularemia associated with infection from fresh water have also been described in France (24, 25) and the USA (26).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations